Scaphoid fractures and non-union: a review of current evidence. Issue 4 (August 2021) - Soufi, Mazen; See, Abbas; Hassan, Sami
Abstract: Scaphoid fractures are common orthopaedic injuries that can have a significant impact on patient wellbeing. Due to its unique anatomy, it is both challenging to diagnose and to treat these injuries without associated complications and sequelae. Treatment options can vary from plaster immobilization to percutaneous fixation but despite significant advances in treatment, non-union remains a complication of these injuries. A scaphoid non-union can lead to significant morbidity in wrist function and the treatment options available are dependent on the stage of disease. The techniques utilized in treating these presentations and their outcomes remain in constant discussion amongst the hand surgery community. This article aims to review some of the current literature that surrounds the treatment of both acute fractures, and non-union in order to inform the trainee hand surgeon.